RETRACTED: Investigating the effect of guide construction on yarn tension - Matismailov S.L.; Aripova Sh.R.; Akhmedov Kamol; Korabayev Sherzod; Makhkamova Sh.F.; Valieva Z.F. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001